2013
DOI: 10.1146/annurev-micro-092412-155614
|View full text |Cite
|
Sign up to set email alerts
|

Archaea in Biogeochemical Cycles

Abstract: Archaea constitute a considerable fraction of the microbial biomass on Earth. Like Bacteria they have evolved a variety of energy metabolisms using organic and/or inorganic electron donors and acceptors, and many of them are able to fix carbon from inorganic sources. Archaea thus play crucial roles in the Earth's global geochemical cycles and influence greenhouse gas emissions. Methanogenesis and anaerobic methane oxidation are important steps in the carbon cycle; both are performed exclusively by anaerobic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
312
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(325 citation statements)
references
References 144 publications
3
312
0
10
Order By: Relevance
“…We were not able to resolve the branching position of SAGMEG within the Euryarchaeota solely on the basis of rRNA phylogenies. The placement of the group is also inconsistent in the literature 4,9 . Therefore, to investigate the phylogenetic position of SAGMEG within the Archaea in more detail, we constructed phylogenetic trees based on concatenated ribosomal proteins ( Supplementary Fig.…”
mentioning
confidence: 99%
“…We were not able to resolve the branching position of SAGMEG within the Euryarchaeota solely on the basis of rRNA phylogenies. The placement of the group is also inconsistent in the literature 4,9 . Therefore, to investigate the phylogenetic position of SAGMEG within the Archaea in more detail, we constructed phylogenetic trees based on concatenated ribosomal proteins ( Supplementary Fig.…”
mentioning
confidence: 99%
“…The binning of nitrogenase transcripts from the LI were to Archaea, including methanogens and ANME. Methanogens are considered to be among the nitrogen-fixing free-living anaerobes (Madigan et al, 2008), and recently it was demonstrated that deep-sea ANME from ammoniumreplete sediments fix N 2 and share the products of nitrogen fixation with sulfate-reducing bacterial partners (Dekas et al, 2009;Offre et al, 2013). We do not have an explanation for why methanogens/ ANME compensate for the energetic burden of diazotrophy in an ammonium-rich environment.…”
Section: Metabolism Of Nitrogen Compoundsmentioning
confidence: 75%
“…Abundances of soil Crenarchaeota also are positively correlated with soil N content (36). Conversely, several reports have shown the potential for members of the Euryarchaeota, which are predominately methanogens, to fix atmospheric N 2 (38,39). This characteristic could place them at a competitive disadvantage under conditions of elevated N availability and explain their strong proportional decrease with N fertilization.…”
Section: Resultsmentioning
confidence: 98%
“…For example, nutrient-induced shifts in copiotrophic vs. oligotrophic traits could have important implications for soil C cycling (52) if their traits elicit effects rather than solely reflect responses (53). Likewise, decreases in mycorrhizae and methanogens could have important impacts on ecosystem-level processes (39,54). This work moves us toward a more mechanistic understanding of how shifts in microbial community composition mediate and reflect the effects of anthropogenically elevated nutrient inputs on terrestrial ecosystems.…”
Section: Discussionmentioning
confidence: 99%